2021
DOI: 10.3390/nu13093121
|View full text |Cite
|
Sign up to set email alerts
|

Korean Red Ginseng Ameliorates Fatigue via Modulation of 5-HT and Corticosterone in a Sleep-Deprived Mouse Model

Abstract: Central fatigue, which is neuromuscular dysfunction associated with neurochemical alterations, is an important clinical issue related to pathologic fatigue. This study aimed to investigate the anti-central fatigue effect of Korean red ginseng (KRG) and its underlying mechanism. Male BALB/c mice (8 weeks old) were subjected to periodic sleep deprivation (SD) for 6 cycles (forced wakefulness for 2 days + 1 normal day per cycle). Simultaneously, the mice were administered KRG (0, 100, 200, or 400 mg/kg) or ascorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Seven-month-old SAMP8 exhibited characteristics of aging such as weight loss and decreased motor function, as well as symptoms of fatigue such as decreased activity. Furthermore, several blood biomarkers, which are known to increase with fatigue, were increased in SAMP8, supporting the idea that they were fatigued [ 32 , 33 ]. Interestingly, there was an increase in IL-1β and a decrease in IL-1RA, both of which are believed to play an important role in fatigue, in both the brain and muscle of aged SAMP8.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Seven-month-old SAMP8 exhibited characteristics of aging such as weight loss and decreased motor function, as well as symptoms of fatigue such as decreased activity. Furthermore, several blood biomarkers, which are known to increase with fatigue, were increased in SAMP8, supporting the idea that they were fatigued [ 32 , 33 ]. Interestingly, there was an increase in IL-1β and a decrease in IL-1RA, both of which are believed to play an important role in fatigue, in both the brain and muscle of aged SAMP8.…”
Section: Discussionmentioning
confidence: 69%
“…In the present study, even though NYT administration was found to reduce fatigue-like conditions, it had no effect on blood biomarkers ( S4 Fig ). Blood biomarkers are also important indicators, and increased biomarkers are associated with fatigue [ 32 , 33 , 47 ]. However, the results of the present study were inconsistent with those of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Panax ginseng, in the family Araliaceae, is considered as one of the most frequently employed medicinal herbs and functional foods [184,185]. In a randomized, placebocontrolled, crossover study, daily consumption of 3 g of Korean red ginseng (KRG) for 4 weeks was shown to improve daytime contrast sensitivity and ocular pain in glaucoma patients [186].…”
Section: Panax Ginseng-ginsenosidementioning
confidence: 99%
“…[ 14 ]. To date, numerous studies have revealed various beneficial effects of P. ginseng and its derivatives, including ginsenosides, for the manipulation of fatigue [ 15 ], diabetes [ 16 ], chronic pain [ 17 ], and systemic inflammation [ 18 ].…”
Section: Introductionmentioning
confidence: 99%